2015
DOI: 10.1021/cg500880m
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition Mechanism of Calcium Oxalate Crystal Growth by Cooperation Influence of Colloidal Selenium Nanoparticles and Bovine Serum Albumin

Abstract: This study investigated the effect of colloidal selenium nanoparticles modified with bovine serum albumin (nanoSe0–BSA) on the crystal phase and morphology of CaC2O4 and explained the cooperative inhibition mechanism of nanoSe0 and BSA on the crystallization of CaC2O4. The results were compared with those for nanoSe0 and BSA individually. NanoSe0 could induce the formation of oval or spherical calcium oxalate monohydrate (COM) crystals at high concentrations. BSA could induce the formation of hexagonal plate-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…The sample crystallized in the absence of the extract was monohydrate form with no other crystalline phases nor phase transformations, and the major diffraction peaks of the sample were in agreement with JCPDS card no: 00-020-0231. As can be seen from the patterns of the crystals, four dominant peaks at 2θ = 14.9, 24.5, 30.1, and 38.3° attributed to the (101), (020), (220), and (130) planes of the monoclinic structure were detected in each pattern, in agreement with the results of previous studies 17 . Materials Analysis Using Diffraction (MAUD) software was utilized to determine the unit cell parameters and detect the crystal system.…”
Section: Figure 1 Ftir Spectrum Of the Avocado Leavessupporting
confidence: 91%
“…The sample crystallized in the absence of the extract was monohydrate form with no other crystalline phases nor phase transformations, and the major diffraction peaks of the sample were in agreement with JCPDS card no: 00-020-0231. As can be seen from the patterns of the crystals, four dominant peaks at 2θ = 14.9, 24.5, 30.1, and 38.3° attributed to the (101), (020), (220), and (130) planes of the monoclinic structure were detected in each pattern, in agreement with the results of previous studies 17 . Materials Analysis Using Diffraction (MAUD) software was utilized to determine the unit cell parameters and detect the crystal system.…”
Section: Figure 1 Ftir Spectrum Of the Avocado Leavessupporting
confidence: 91%
“…Besides, the nanoselenium used in their study was synthesized using chemical reduction of selenious dioxide with ascorbic acid and also using leaf extract of Ocimum tenuiflorum. For example, Liang et al, 2009 andLiang et al, 2020 reported the modulation using 2.3 µg ml −1 of nanoselenium while a similar modulation of size and shape was achieved using 22 µg ml −1 (Zhong et al, 2015). The use of urolithiatic molecules such as phytic acid and chit molecules conjugated with gallic acid (Chit-Gal) are reported for treatment of urolithiasis but limited due to the expensive synthesis involved (Ahmed et al, 2016;Queiroz et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…SeNPs are also reported for their importance in medical applications due to their different properties such as enhanced biocompatibility (Barnaby et al, 2011), photoconductive (Luo et al, 2009), antiproliferative (Srivastava et al, 2014), antigenotoxic (Prasad & Selvaraj, 2014) and their ability to modulate the shape of calcium oxalate crystals (Liang et al, 2009;Zhong et al, 2015). In recent times, nanoselenium has also been reported to exhibit lower toxicity in humans than its inorganic or organic form (Zhang & Spallholz, 2011), possibly because of its good antioxidant properties (Prasad et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Both COM and COD were found existing in human urine . Prior to the formation of calcium oxalate crystals, amorphous calcium oxalate (ACO) is formed initially after nucleation, , which are aggregated by clusters formed in prenucleation process. , Because the components of urine is complex, based on kidney stones, many studied have focused on the effects of different additives, , such as proteins (osteopontin, Tamm-Horsfall protein, albumin, and lysozyme), small molecules (citrate and hydroxycitrate), and inorganic salts on the nucleation and growth of calcium oxalate.…”
Section: Introductionmentioning
confidence: 99%